The 1974 West Flank Eruption of Mount Etna: A Data-Driven Model for a Low Elevation Effusive Event - Lormand, Charline; Harris, Andrew J. L.; Chevrel, Magdalena Oryaëlle; Calvari, Sonia; Gurioli, Lucia; Favalli, Massimiliano; Fornaciai, Alessandro; Nannipieri, Luca (Frontiers in Earth Science, 2020)
Low elevation effusive eruptions on flanks of polygenic volcanoes represent highly hazardous events due to their location near, or in, communities. Their potentially high effusion rates can also feed fast moving lava flows, that can enter populated areas with little time for warning or evacuation as was the case at Nyiragongo in 1977. The January-March 1974 eruption on the western flank of Mount Etna, Italy, was a low elevation effusive event, but with low effusion rates. It consisted of two eruptive phases separated by a 23 days quiescence and produced two adjacent lava flow fields. This study describes the different properties of the two lava flow fields through structural and morphological analyses of the lava flows using UAV-based photogrammetry overflights and detailed textural and rheological analyses of the samples collected. Phase I produced lower density (∼2210 kg m-3) and crystallinity (∼37 %) lavas at higher eruption temperatures (~1080 °C) and formed thinner (2-3 m) lava flow units with poorly-developed channels than Phase II. Although Phase II involved an identical source magma, it yielded higher densities (∼2425 kg m-3) and crystallinities (∼40 %), and lower eruption temperatures (~1030 °C), forming thicker (5 m) lava flow units with well-formed channels. These contrasting properties were associated with distinct rheologies, Phase I lavas having a lower viscosity (∼103 Pa s) than that of Phase II (∼105 Pa s). Effusion rates were higher during Phase I (≥5 m3/s), but the episodic, short-lived nature of each lava flow emplacement event meant that flows were volume-limited and shorter than 1.5 km. Phase II effusion rates were lower (≤4 m3/s), but sustained effusion led to flow units that could still extend to 1.3 km. A petrologically-based model is thus presented whereby a similar magma fed both phases, but slower ascent during Phase II may have led to higher degassing- and cooling-induced densities and crystallinities, and lower temperatures. We here define a low effusion rate end-member event-scenario for low elevation effusive events, revealing that such events are not necessarily of high effusion rate and velocity feeding extensive lava flow fields, as in the catastrophic event scenarios of Etna 1669.